Estado securitário, biopolítica e atuação do judiciário - Messias, Gretha Leite Maia de (2013)
This thesis has as its object a critical study of the Brazilian Judiciary’s performance in face of legal disputes involving practices of bio-politics. Practices of bio-politics means the intervention of the State in which the basic biological features of the human being become part of a general strategy of power. The research is justified by the increase of legal disputes involving border scramble caused by biotechnology. Biotechnology is defined as any process leading to technological application in biological systems. These legal disputes require the Judiciary to produce a discourse about bio-politics. As a first hypothesis, the thesis considers that the definition of a state model is crucial to the expansion of bio-political practices. To test the first hypothesis, the thesis systematizes the concepts of the Rule of law, the theoretical proposals and the historical experiences of the liberal state, the social state, the totalitarian state and the security state, and investigates the Judiciary within these four mentioned features. As a second hypothesis, the thesis considers that the complexity around issues of bio-politics extends the possibilities of malfunction in law itself, which leads to difficulties in the Judiciary performance. In order to ratify the second hypothesis, this thesis presents the thoughts of Hannah Arendt, Michel Foucault and Giorgio Agamben, and systematizes the main discourses that contributed to “judicialize bio-politics”, which are the gender discourse, the humanizing function of the law (proposal formulated by legal contemporary Anthropology) and the juridical discourse of individual rights. Through a critical analysis of the reasoning of Court decisions, this thesis investigates what the Judges think about the Law, bio-politics and its problems, with qualitative analysis of decisions that affect human sexuality. The thesis concludes that the proposal of a security State extends spaces and opportunities for the practices of bio-politics. It also concludes that the complexity of the issues complicates the Judiciary’s performance, considering the Rule of law. This thesis aims at recovering the importance of the law as a tool to reduce complexity, reordering biological or moral arguments in this debate, with the purpose of producing judiciary decisions more in line with the framework of the rule of law.